2003
DOI: 10.1897/02-173
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal differentiation in frogs exposed to estrogenic and antiestrogenic compounds

Abstract: Exposure of amphibians to endocrine disrupting compounds (EDCs) may alter differentiation of gonads, especially when exposures begin during early life stages. Gonadal differentiation was observed in leopard frogs (Rana pipiens) and wood frogs (Rana sylvatica) exposed as tadpoles to estrogenic (estradiol, ethinylestradiol, nonylphenol) and antiestrogenic compounds (an aromatase inhibitor, flavone, and an antiestrogen, ICI 182780). Exposure to all compounds at micrograms/L concentrations altered gonadal differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 53 publications
4
75
2
Order By: Relevance
“…We observed that EE2 did not significantly affect the survival of the X. laevis tadpoles, which were the same with other amphibians, such as M. ornate, L. pipiens (MacKenzie et al, 2003;Mali and Gramapurohit, 2016). In present study, 1 nM EE2 prolonged the time to reach stage 58 of X. laevis (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…We observed that EE2 did not significantly affect the survival of the X. laevis tadpoles, which were the same with other amphibians, such as M. ornate, L. pipiens (MacKenzie et al, 2003;Mali and Gramapurohit, 2016). In present study, 1 nM EE2 prolonged the time to reach stage 58 of X. laevis (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…f For C. riparius, a worst-case NOEC of 100 ng EE2/L is used, based on the unbounded LOEC of >100 ng EE2/L. g For amphibians, the relatively high unbounded values of <1000 ng EE2/L for the frogs R. pipiens and R. sylvatica (62) and <784 ng EE2/L for the frog X. (Silurana) tropicalis (61) were discarded from the data set.…”
Section: Nash Et Al 2005mentioning
confidence: 99%
“…In these species, estrogen is the ovary-determining factor. Estrogen treatment of male embryos during the critical period of development in fish (Guiguen et al, 1999;Kobayashi et al, 2003), frogs (Mackenzie et al, 2003;Kato et al, 2004), reptiles (Pieau and Dorizzi, 2004), chicks (Abinawanto et al, 1996;Mittwoch, 1998;Akazome and Mori, 1999), or in marsupial newborns (Shaw et al, 1988;Baker et al, 1993;Fadem, 2000;Coveney et al, 2001;Renfree et al, 2001) can cause testis-to-ovary sex reversal. In addition, inhibition of estrogen synthesis in female embryos leads to testis development in these species.…”
Section: Maintenance Of Ovarian Differentiation: Essential Roles Of Ementioning
confidence: 99%